A New Orchid Species of Dendrobium Sect. Calcarifera from Terengganu, Peninsular Malaysia (Orchidaceae: Dendrobiinae) - Besi, Edward Entalai; Nikong, Dome; Mustafa, Muskhazli; Go, Rusea (Phytotaxa, 2018)
Dendrobium mizanii, a new species to science belonging to Dendrobium Sect. Calcarifera was discovered in a summit region of a disturbed montane forest in Setiu, Terengganu, and named after His Majesty Sultan of Terengganu, Tuanku Mizan Zainal Abidin. A description, illustration, field and comparison with the closely related species D. crocatum from Peninsular Malaysia and D. doloissumbinii from Borneo are provided here.